Valorisation of research results in the Mediterranean region - Menéndez A. (Moving forward in the Euro-Mediterranean Research and Innovation partnership. The experience of the MIRA project, 2013)
The efficient use of the existing research capabilities in the public sector to support the economic and social development in the Mediterranean Partner Countries (MPCs) is a key challenge. Valorisation of research, a fashionable topic, can strongly contribute provided that the research objectives and results are close to the strategic needs and prospects of firms. As the innovation policies in MPCs are increasingly dealing with valorisation, the article describes some of the measures and instruments created, namely technology transfer units, underlining the importance of analysing valorisation under a large focus which considers the conditions of public research and industry as well as the linkages between them.